Haploid genetic screens identify SPRING/C12ORF49 as a determinant of SREBP signaling and cholesterol metabolism - Loregger, Anke; Raaben, Matthijs; Nieuwenhuis, Joppe; Tan, Josephine M. E.; Jae, Lucas T.; van den Hengel, Lisa G.; Hendrix, Sebastian; van den Berg, Marlene; Scheij, Saskia; Song, Ji-Ying; Huijbers, Ivo J.; Kroese, Lona J.; et al. (Nature communications, 2020)
The sterol-regulatory element binding proteins (SREBP) are central transcriptional regulators of lipid metabolism. Using haploid genetic screens we identify the S REB P R egulat in g G ene ( SPRING/C12ORF49 ) as a determinant of the SREBP pathway. SPRING is a glycosylated Golgi-resident membrane protein and its ablation in Hap1 cells, Hepa1-6 hepatoma cells, and primary murine hepatocytes reduces SREBP signaling. In mice, Spring deletion is embryonic lethal yet silencing of hepatic Spring expression also attenuates the SREBP response. Mechanistically, attenuated SREBP signaling in SPRING KO cells results from reduced SREBP cleavage-activating protein (SCAP) and its mislocalization to the Golgi irrespective of the cellular sterol status. Consistent with limited functional SCAP in SPRING KO cells, reintroducing SCAP restores SREBP-dependent signaling and function. Moreover, in line with the role of SREBP in tumor growth, a wide range of tumor cell lines display dependency on SPRING expression. In conclusion, we identify SPRING as a previously unrecognized modulator of SREBP signaling. The transcription factor SREBP is a well-studied and major regulator of sterol and fatty acid metabolism. Here, the authors used haploid genetic screens to identify the Golgi-resident protein SPRING as a new modulator of SREBP by regulating the level of functional SREBP cleavage-activating protein (SCAP).